RELATIONSHIP OF EARPHONE USAGE WITH THE EMERGENCE OF HEARING LOSS AND HEALTH PROBLEMS IN MEDICAL STUDENTS OF SOUTH PUNJAB - IMRAN, N; SHEIKH , MA; AHMER , S; RAZA , M; QURESHI , MZ; HUSSAIN , SA (Biological and Clinical Sciences Research Journal, 2024)
Noise induced hearing loss (NIHL) is a rising concern, particularly in the young adult population who frequently use personal listening devices (PLDs) such as earphones. Medical students are at risk of having hearing related problems due to the high usage of PLDs for both academic and recreational purposes. This study aimed to assess the prevalence of hearing loss, symptoms associated with earphone use, and the relationship between earphone usage patterns and hearing thresholds among medical students in South Punjab, Pakistan. Objective: To evaluate the prevalence of hearing loss and associated symptoms (headache, tinnitus, otalgia, fatigue) about earphone usage habits, including daily duration, volume, and frequency of use, among undergraduate medical students. Methods: This cross sectional study was conducted at Nishtar Medical University and CMH Institute of Medical Sciences (CIMS), Multan from October 2023 to August 2024. A total of 267 medical students aged 18 26 years participated in this study. Participants were categorized into two groups: mild users (≤1 hour/day) and Intense users (>1 hour/day) of PLDs. Data were collected using a self administered questionnaire on demographics, earphone usage patterns, and associated symptoms. Audiometric testing was performed using Pure Tone Audiometry (PTA) to assess hearing thresholds at 250 Hz to 8000 Hz. Descriptive statistics, t tests, chi square tests, and Pearson correlation were used to analyze the data. Results: The majority of participants (55.4%) were aged 21 23 years, with a balanced gender distribution (52.4% male, 47.6% female). Intense users (53.2%) had significantly higher hearing thresholds at all frequencies compared to mild users, particularly at higher frequencies (4000 Hz and 8000 Hz). In the right ear, the prevalence of hearing loss is 3.2% for mild users and 13.3% for intense users whereas in the left ear, it is 4.8% and 12.7% for mild and intense users respectively. The most common form of hearing loss was mild sensorineural hearing loss at 4000Hz. Intense users reported higher rates of symptoms, including headache (35.9% vs. 16%), fatigue (47.2% vs. 17.6%), otalgia (46.5% vs. 22.4%), and tinnitus (34.5% vs. 17.6%), with statistically significant associations between symptom prevalence and usage duration and volume. Conclusion: Prolonged earphone usage is significantly associated with the emergence of hearing loss and increased prevalence of auditory symptoms among medical students. Despite being aware of the risks, many students do not follow safe listening practices, underscoring the need for educational initiatives. Promoting the "Rule of 60" and encouraging regular breaks during usage are essential steps to mitigate the risk of NIHL.